2018
DOI: 10.1002/ijgo.12624
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in women's cancer care: Global challenges and advances

Abstract: Women's cancer rates are increasing in low‐ and middle‐income countries, with presentations that are often far advanced requiring intense symptom management, thus advancing the urgent need to address palliative care. Most resource settings have some options available to assist women with advanced gynecologic cancer, and a combination of leveraging these and expanding on emerging models for palliative care could lessen suffering and improve care for women with gynecologic cancers globally. Providing palliative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…They described loss of dignity when feeling neglected, invaded in their personal lives and offended by HCPs. These findings are also supported by several studies of women sensing insecurity and experiencing violation in their everyday lives (Aabom et al, 2005;Cain & Denny, 2018;Poulose et al, 2013). The findings resonate with the theoretical perspective of suffering related to care as proposed by Eriksson (1994).…”
Section: Discussionsupporting
confidence: 86%
“…They described loss of dignity when feeling neglected, invaded in their personal lives and offended by HCPs. These findings are also supported by several studies of women sensing insecurity and experiencing violation in their everyday lives (Aabom et al, 2005;Cain & Denny, 2018;Poulose et al, 2013). The findings resonate with the theoretical perspective of suffering related to care as proposed by Eriksson (1994).…”
Section: Discussionsupporting
confidence: 86%
“…Previous research from Norway and Scotland has revealed that healthcare services do not meet the demands of care of older home-dwelling cancer patients, implying a risk of hindering older people's access to proper end-of-life care (Fjose et al, 2018;Miller & Nevadunsky, 2018). Another risk relates to older people being considered as one group without appreciation of gender differences related to life-threatening illnesses (Cain & Denny, 2018;Rochon et al, 2020). Whereas dignity in care has been discussed from the perspective of HCPs in general (Baillie et al, 2008;Barclay, 2016;Johnston et al, 2012), we found that GPs, CCs and HCPNs emphasized sources of dignity differently.…”
Section: Discussionmentioning
confidence: 99%
“…Breast, colorectal and lung cancers accounted for the top three of women's cancers, with breast cancer representing the leading cause of death (Bray et al, 2018). Providing palliative care for women with cancer seems to be hampered by lack of both human and physical resources as well as policy absence or barriers (Cain & Denny, 2018). Palliative care is a widely used term within cancer care, and may be provided to the patient at any point from diagnosis to end-of -life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations